Samuel Fisher papers - Fisher, Samuel, approximately 1732-1816.
Diary of Samuel Fisher, kept during operations around Lake George (1758 June 23-July 12) during the French and Indian War and a volume of mounted papers (circa 1760-1790).
Army officer.
Collection material in English.
Keywords: George, Lake (N.Y. : Lake) -- History; New York (State) -- History -- French and Indian War, 1754-1763.; United States -- History -- French and Indian War, 1754-1763.